Secular religiosity in Chinese politics: A Confucian perspective - TAN, Sor-hoon (Institutional Knowledge at Singapore Management University, 2010)
The concept of a secular state is important in many parts of Asia and how this is resolved has important implications for the social, economic and political development of various Asian countries. Unfortunately, problems of the secular state have all along been studied based on the historical experience of state formation in Europe, with little (or no) input from the Asian perspective. This book will for the very first time, present mainly Asian perspectives, while drawing on Western experience as well. Conceptual issues are discussed together with detailed accounts on how different countries and traditions understand and seek to implement the ideas of a secular state.